Impact assessment of ecological environment governance on the green development efficiency - Xiao Guan; Weimin Zhang (Sustainable Futures)
Ecological environment governance is a key driver to promote green development and build a beautiful China. This study practically examines the influence of ecological environment governance on green development efficiency using a two-way fixed panel model using a dataset comprising 120 municipalities at the prefecture level in China including the years 2008 to 2022. It is found that ecological environment governance can enhance green development efficiency. meanwhile, industrial structure higher is a mediating pathway for ecological environment governance to affect green development efficiency, and digital infrastructure positively moderates the impact of ecological environment governance on green development efficiency as well as the mediating effect of industrial structure higher. In addition, there is persistence and heterogeneity in the effect of ecological environment governance on green development efficiency, and the boosting effect of ecological environment governance on green development efficiency is particularly evident across in the east of the Hu Huanyong Line, key ecological function areas and resource-driven cities.